2014
DOI: 10.1016/j.livsci.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Live yeast (Saccharomyces cerevisiae var. boulardii) supplementation in fattening rabbit diet: Effect on productive performance and meat quality

Abstract: The nutrient digestibility coefficients of each diet were determined in the second week of the 105 growing trial (with 10 rabbits aged 44d). The faeces were individually collected for five days using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
(17 reference statements)
3
21
1
Order By: Relevance
“…No significant effect of probiotic supplementation was observed on carcass traits (Table 4). Rabbits in all dietary groups had similar dressing yield (average 58%), which corroborate well with the earlier reported values Rotolo et al 2014). Besides, a measure of caecum weight and the epithelial layer thickness were assessed, which revealed relatively higher weight and a significantly increased thickness in both the probiotics-supplemented groups than the control.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…No significant effect of probiotic supplementation was observed on carcass traits (Table 4). Rabbits in all dietary groups had similar dressing yield (average 58%), which corroborate well with the earlier reported values Rotolo et al 2014). Besides, a measure of caecum weight and the epithelial layer thickness were assessed, which revealed relatively higher weight and a significantly increased thickness in both the probiotics-supplemented groups than the control.…”
Section: Resultssupporting
confidence: 92%
“…Some authors reported that probiotics can influence GI weight and the relative proportion of its organs and also the microbial fermentation pattern in the ceacum . Rotolo et al (2014) observed similar caecum weight as percentage of total BW. Proliferation of colonocytes in response to prebiotic effects of hemicelluloses and colonization of supplemental probiotics might have contributed to thickening of mucosa without hindering the nutrient absorption process.…”
Section: Resultsmentioning
confidence: 55%
“…Kimsé et al (2012) and Rotolo et al (2014) did not report any effect of live yeast (Saccharomyces cerevisiae) on volatile fatty acid molar proportions. Furthermore, Maertens et al (1994) and Bonai et al (2008) did not note any effect of Bacillus on the fermentation pattern.…”
mentioning
confidence: 97%
“…The counts of coliforms and total aerobic bacteria in caecum were low. Related to the effect of yeast supplementation on slaughter traits, Rotolo et al (2014) reported no effect on the weight of the full and empty caecum. However, Maertens et al (1994) observed that caecal weight was higher in rabbits fed the Paciflor ® (Bacillus) diet.…”
mentioning
confidence: 99%
“…Supplementation with alternative substances, such as probiotics, prebiotics, enzymes and organic acids, has been studied in rabbits, with interesting results emerging (Falcão-e-Cunha et al, 2007;Rotolo et al, 2014). However, the number of phyto-studies remains limited (Botsoglou et al, 2004;Krieg et al, 2009;Arafa et al, 2010;Simonová et al, 2010;Ayala et al, 2011;Szabóová et al, 2012;Rotolo et al, 2013).…”
mentioning
confidence: 99%